Talking heads : the neuroscience of language - Denes, G. (Hove, East Sussex [England] : Psychology Press, 2011)
"The origin, development, and nature of language has been the focus of theoretical debate among philosophers for many centuries. Following the discovery 150 years ago that language is a biological system, an increasing number of neuroscientists began to search for its anatomical basis and its links with other such systems. The relatively recent introduction of neuroimaging tools, such as PET and MRI, has brought rapid and groundbreaking developments to the field of Neurolinguistics. In this book, Denes and Smith harness these advances to adopt a biolinguistic approach to the study of a subject that increasingly sees the collaboration of linguists, experimental psychologists, neuroscientists and clinicians. Following an up-to-date description of acquired language disorders, and their contribution to the design of a functional architecture of language, the book illustrates the neurological process involved in the production of written language, as well as investigating the neurological systems responsible for sign language production and second language acquisition. Talking Heads reviews the latest research on the nature, structure and origin of language to provide a concise analysis of the multifaceted aspects of language which focuses both on theoretical aspects and physical implementation. With a glossary of the anatomical and linguistic terms, this book provides an invaluable resource to undergraduate and graduate students of Psychology, Psycholinguistics and Linguistics. It will also be of interest to neurologists, speech therapists and anyone interested in the mind-brain problem"--Provided by publisher.
(Publisher-supplied data) CHAPTER 1 DEFINING LANGUAGE -- CHAPTER 2 THE ORIGIN AND EVOLUTION OF LANGUAGE -- CHAPTER 3 THE ANATOMY OF LANGUAGE -- CHAPTER 4 ACQUIRED LANGUAGE DISORDERS: THE APHASIAS -- CHAPTER 5 THE SOUNDS OF LANGUAGE: THE PRODUCTION AND COMPREHENSION OF WORDS -- CHAPTER 6 THE WORDS TO SAY IT: THE FUNCTIONAL AND NEUROLOGICAL ARCHITECTURE OF THE LEXICAL SYSTEM -- CHAPTER 7 THE TRAINS OF LANGUAGE: SYNTAX AND MORPHOLOGY -- CHAPTER 8 THE NEUROLOGICAL BASES AND FUNCTIONAL ARCHITECTURE OF WRITTEN LANGUAGE -- CHAPTER 9 THE NEUROLOGICAL BASES AND FUNTIONAL ARCHITECTURE OF BILINGUALISM -- CHAPTER 10 SPEAKING WITH OUR HANDS: SIGN LANGUAGE -- CHAPTER 11 LANGUAGE ACQUISITION AND DEVELOPMENTAL LANGUAGE DISORDERS.
"Authorized translation from Italian language ed. published by Zanichelli."
First published 2009 by Zanichelli, Italy.
Includes bibliographical references and indexes.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Neurolinguistics; Language disorders; Psycholinguistics; Electronic books